2013
DOI: 10.1071/fp12309
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest responses to increasing atmospheric CO2: current knowledge and opportunities for future research

Abstract: Abstract. Elevated atmospheric CO 2 concentrations (c a ) will undoubtedly affect the metabolism of tropical forests worldwide; however, critical aspects of how tropical forests will respond remain largely unknown. Here, we review the current state of knowledge about physiological and ecological responses, with the aim of providing a framework that can help to guide future experimental research. Modelling studies have indicated that elevated c a can potentially stimulate photosynthesis more in the tropics than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
117
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 240 publications
(306 reference statements)
1
117
2
Order By: Relevance
“…Tropical forests supply an estimated 9% of the global demand for timber and wood products [2,3], and the production and processing of these makes a significant contribution to incomes and employment in many tropical countries. However, current global concerns for tropical forests focus largely on carbon-they account for about half the total biomass carbon in the terrestrial biosphere and a third of global terrestrial carbon fluxes [4]-and biodiversity-they are believed to support more than half of global terrestrial biodiversity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tropical forests supply an estimated 9% of the global demand for timber and wood products [2,3], and the production and processing of these makes a significant contribution to incomes and employment in many tropical countries. However, current global concerns for tropical forests focus largely on carbon-they account for about half the total biomass carbon in the terrestrial biosphere and a third of global terrestrial carbon fluxes [4]-and biodiversity-they are believed to support more than half of global terrestrial biodiversity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that tropical C storage may be strongly determined by the hyperdominance (Fauset et al, 2015) and functional composition of tropical tree communities in association with different life-history strategies of tropical trees (Fauset et al, 2012). A CO 2 induced shift to shorter average tree life span could favor fast-growing tree species that invest in low-cost tissue, which could increase the turnover of C and thus decrease the C storage at the landscape scale (Phillips et al, 2009;Fauset et al, 2012;Cernusak et al, 2013). In accordance, simulations of nonrandom species loss for fast-growing species with low wood density increased C storage by 10%, whereas the loss of high statured slow-growing species decreased C stocks by over 30% (Bunker, 2005).…”
Section: The Way Forward: Model-experiments Integrationmentioning
confidence: 99%
“…Efforts to quantify the response of aboveground carbon storage derived from forest inventory plots concluded that such events have the potential to reverse a multi-decadal biomass C sink across Amazonia (Phillips et al, 2009). However, to date predicted responses of the Amazon forest to projected global climate changes (mainly precipitation and temperature) remain largely speculative due to a lack of direct experimental evidence Davidson et al, 2012;Cernusak et al, 2013). As a surrogate, ecosystem models that include the mechanistic representation of key ecosystem processes, such as photosynthesis, respiration, growth, and C allocation, have been used for projections of ecosystem responses to changes in climate, atmospheric CO 2 and nutrient availability (e.g., Goll et al, 2012;Huntingford et al, 2013;Joetzjer et al, 2014;Smith et al, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations